IMPLEMENTASI APLIKASI DATA MINING DALAM PENGAMBILAN MATAKULIAH YANG BERPENGARUH PADA RENDAHNYA INDEKS PRESTASI KUMULATIF DENGAN METODE ASOSIASI MENGGUNAKAN ALGORITMA FP-GROWTH (STUDI KASUS: INSTITUT BISNIS DAN INFORMATIKA KWIK KIAN GIE) - Sigit Birowo Elis Sondang D (Jurnal Informatika dan Bisnis, 2016)
Along with the development of technology in education and human needs in something that is instant, fast, and accurate, campus Kwik Kian Gie School of Business uses the analysis of data mining on the students' scores to determine the course that will influence performance index was below average. This analysis process can support decision-making on related subjects. The results of this research is the analysis of data mining association about subjects that affect GPA students to be low. The conclusion of this study showed that association analysis data mining can help the college to see the value of the subjects which affect Grade Students to be low.Keywords: Data Mining, Association, FP-Growth, GPA, Values, Students